APPLICATION OF COOPERATIVE LEARNING MODEL TYPE OF NHT (NUMBERED HEADS TOGETHER) TO INCREASE BIOLOGY LEARNING OUTCOMES IN PHOTOSYNTHETIC MATERIALS OF STUDENTS OF CLASS XII MIPA STATE 12 SMA NEGERI 12 BANDA ACEH - Islamiah Islamiah Islamiah (Jurnal Biologi Sains dan Kependidikan, 2022)
Research has been carried out on the application of a structured numbered heads together type of cooperative learning model to improve biology learning outcomes in photosynthetic material for students of class XII MIPA.3 SMAN 12 Banda Aceh. The aims of this research are: (1) To determine student learning outcomes in studying cells through cooperative learning type NHT, (2) to determine the activities of teachers and students during the teaching and learning process using the cooperative learning model type NHT and (3) to see student learning responses after the application of the learning model NHT cooperative type. This research was conducted at SMAN 12 Banda Aceh from September 25 to October 2, 2019. Subjects in this study were 11 students of class XII MIPA male and 18 female students. This research is a classroom action research (CAR) using two cycles. The research results obtained from observation sheets, questionnaires, and tests were analyzed using the percentage formula. The results of the research on teacher activity in the first cycle were 78.15% and in the second cycle 93.76%, student activity in the first cycle was 70.11% and in the second cycle 85.16% and the test results showed an increase from 66.21% in the first cycle to 82.07% in cycle II. Meanwhile, the students' response to the application of the NHT type of cooperative learning model was very good, reaching 87.19%. Based on the research, it can be concluded that the application of the NHT type of cooperative learning model can improve biology learning outcomes in the photosynthesis material of the XII MIPA class students at SMAN 12 Banda Aceh.